2017
DOI: 10.1021/acs.inorgchem.7b01415
|View full text |Cite
|
Sign up to set email alerts
|

Heteroleptic Fe(II) Complexes with N4S2 Coordination as a Platform for Designing Spin-Crossover Materials

Abstract: Heteroleptic complexes [Fe(bpte)(bim)]X and [Fe(bpte)(xbim)]X (bpte = S,S'-bis(2-pyridylmethyl)-1,2-thioethane, bim = 2,2'-biimidazole, xbim = 1,1'-(α,α'-o-xylyl)-2,2'-biimidazole, X = ClO, BF, OTf) were prepared by reacting the corresponding Fe(II) salts with a 1:1 mixture of the ligands. All mononuclear complexes exhibit temperature-induced spin crossover (SCO) with the onset above room temperature. The SCO is rather gradual, due to low cooperativity of interactions between the cationic complexes, as reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…The average Fe-N bond length of 1.990 Å and Fe-S bond length of 2.264 Å in C1 (@173 K) are in accordance with those reported in literature and account for an iron(II) ion in the [LS] state [23][24][25][26][27][28][29]. Figure S7 shows the crystal structure/asymmetric unit of C1 (@173 K).…”
Section: Crystal Structuressupporting
confidence: 85%
“…The average Fe-N bond length of 1.990 Å and Fe-S bond length of 2.264 Å in C1 (@173 K) are in accordance with those reported in literature and account for an iron(II) ion in the [LS] state [23][24][25][26][27][28][29]. Figure S7 shows the crystal structure/asymmetric unit of C1 (@173 K).…”
Section: Crystal Structuressupporting
confidence: 85%
“…The most widely studied SCO system is iron(II) complexes where the metal centre is surrounded by six nitrogen donors, however there are fewer examples of other metal centres and geometries [13–16] . In addition to the N 6 coordination sphere, recently, it has been demonstrated that N 4 S 2 systems can produce iron(II) SCO‐active complexes, with only a handful of ligands that can provide the right ligand field for SCO to occur, [17–23] Figure 1. All the S‐based ligands contain the same thioether functional group, in combination with amine, pyridine, triazole or pyrazole nitrogen donors, and some of them contain NCE (E=S, Se or BH 3 ) co‐ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[41][42][43][44][45] Among them, mononuclear or dinuclear complexes based on thioether ligands, with FeN 4 S 2 coordination sphere, have been shown to exhibit original transitions such as multi-step cooperative SCO behaviour. [41][42][43][44] Concerning Fe(II) complexes with FeN 5 S coordination sphere, very few examples have been investigated, [45][46][47][48][49] and to the best of our knowledge, only one example, [{Fe(tpc-OH)(NCS)(μ-NCS)} 2 ](PrOH) 2 (2), exhibits a SCO behaviour. 45 The latter is a dinuclear SCO Fe(II) complex based on the tripodal ligand tris(2-pyridyl)methanol (see scheme 1, R = H) for which the Fe(II) ions are connected by a pair of end-to-end thiocyanato bridges (-N:S-SCN coordination mode) in a head-to-tail configuration.…”
Section: ■Introductionmentioning
confidence: 99%